Servizi ecosistemici, servizio idrico integrato e componenti tariffarie: l’opportunità dei Payments for Ecosystem Services (2020)
Having defined the possible relationships between ecosystem services and local public services, the text focuses on the integrated water service, illustrating the regulatory tools that contemplate the "environmental and resource costs" that each user must bear as a principle. A wide examination of national and international cases on the use of Payments for Ecosystem Services for the management of water in a multifunctional perspective highlights the opportunity to raise this tariff component to finance ecosystem services in the territorial field.